2017
DOI: 10.1186/s12906-017-1904-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and in vitro anthelmintic activity of Lophira lanceolata (Ochnaceae) on the bovine parasite Onchocerca ochengi and on drug resistant strains of the free-living nematode Caenorhabditis elegans

Abstract: BackgroundOnchocerciasis is one of the tropical neglected diseases (NTDs) caused by the nematode Onchocerca volvulus. Control strategies currently in use rely on mass administration of ivermectin, which has marked activity against microfilariae. Furthermore, the development of resistance to ivermectin was observed. Since vaccine and safe macrofilaricidal treatment against onchocerciasis are still lacking, there is an urgent need to discover novel drugs. This study was undertaken to investigate the anthelmintic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Moreover, animals treated with 10 mg/mL had reduced survival under stress, and their body length indicated that the CEE at this concentration is toxic to the worms. Our results showed that the CEE at 10 mg/mL affected the worm’s life span and development, raising some hypotheses: firstly, since the CEE is a mixture of molecules including rutin, which has antimicrobial activity, this may affect the OP50 E. coli growth and consequently the C. elegans ingestion [4,44,47]; secondly, rutin or tannins present in the CEE may react with the proteins or glycoproteins present in the C. elegans cuticle and affect the development and life span of the worm [48,49]; and lastly, a third scenario could postulate that the CEE antioxidant activity at 10 mg/mL reduces ROS production to a deleterious level, creating an unbalanced REDOX state in the worm. These hypotheses may explain why the CEE was able to affect stress resistance and worm development, despite reducing the basal ROS level.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, animals treated with 10 mg/mL had reduced survival under stress, and their body length indicated that the CEE at this concentration is toxic to the worms. Our results showed that the CEE at 10 mg/mL affected the worm’s life span and development, raising some hypotheses: firstly, since the CEE is a mixture of molecules including rutin, which has antimicrobial activity, this may affect the OP50 E. coli growth and consequently the C. elegans ingestion [4,44,47]; secondly, rutin or tannins present in the CEE may react with the proteins or glycoproteins present in the C. elegans cuticle and affect the development and life span of the worm [48,49]; and lastly, a third scenario could postulate that the CEE antioxidant activity at 10 mg/mL reduces ROS production to a deleterious level, creating an unbalanced REDOX state in the worm. These hypotheses may explain why the CEE was able to affect stress resistance and worm development, despite reducing the basal ROS level.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plants with anthelmintic activities contain phytochemicals, such as polyphenols, tannins, flavonoids, and saponins. This anthelmintic activity may be attributed to an individual or a combined effect of the bioactive compounds (14).…”
Section: Discussionmentioning
confidence: 99%
“…This anticoccidial activity could be attributed to an individual or a combined effect of the bioactive compounds [72]. These constituents could play many beneficial-associated properties such as antioxidant and anti-inflammatory effects associated with compounds rich in bioactive elements (e.g., polyphenolic) [73,74].…”
Section: Discussionmentioning
confidence: 99%